2005
DOI: 10.1093/rheumatology/keh643
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-A1 phototherapy modulates Th1/Th2 and Tc1/Tc2 balance in patients with systemic lupus erythematosus

Abstract: According to the literature, IFN-gamma has a pathogenic role in the development of SLE. We observed a decreased proportion of IFN-gamma-secreting cells, which we think is presumably one of the beneficial effects of UVA1 therapy. On the basis of our study, UVA1 phototherapy does seem to be an effective adjuvant in the treatment of SLE patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2007
2007
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 22 publications
0
40
0
1
Order By: Relevance
“…15) may at least in part be due to the generation of oxidized lipids in the skin. Some of the benefits of UVA-1 phototherapy include a decrease of T cells by UV-induced apoptosis (57) and a decrease in the Th1/ Th2 cell ratio in the inflamed tissue (58). In this context it is interesting that we previously demonstrated that oxidized phospholipids limit the capacity of DC to stimulate T cells to initiate Th-1 responses (29).…”
Section: Discussionmentioning
confidence: 99%
“…15) may at least in part be due to the generation of oxidized lipids in the skin. Some of the benefits of UVA-1 phototherapy include a decrease of T cells by UV-induced apoptosis (57) and a decrease in the Th1/ Th2 cell ratio in the inflamed tissue (58). In this context it is interesting that we previously demonstrated that oxidized phospholipids limit the capacity of DC to stimulate T cells to initiate Th-1 responses (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, in a subgroup of patients with severe lupus nephritis, the intracellular cytokine ratio shifts to a Th1 phenotype [44, 45]. In disease-alleviated SLE patients, decreased IFN- γ -producing cells and increased IL-4-producing CD4 + T cells were observed after corticoid treatment [43] and low-dose UV phototherapy [46], respectively. Although Th1/2-related cytokines might contribute to SLE progression and severity, the cytokine profiles of activated iNKT cells from SLE patients are yet to be determined.…”
Section: Function Of Inkt Cells Associated With Sle Diseasementioning
confidence: 99%
“…As to mechanisms, the therapy reportedly lowers levels of anticardiolipin antibodies 5, as in this patient, these having being cited as contributory to pulmonary hypertension 6; it lowers SSA antibodies 7, characteristically elevated in the ILD of SLE 8; it decreases proportions of cells producing interferon-gamma 9, a major effector molecule in S LE 10; and it promotes macrophage function, impaired in SLE and needed to remove apoptotic bodies, the diminished clearance of which is thought to be central in SLE 5, 11. However, what seems most germane in the specific action of UV-A1 photons on ILD and PH is its unique capacity to generate singlet oxygen, a reactive oxygen species that activates the production of heme oxygenase-1 (HO-1) 12.…”
Section: Discussionmentioning
confidence: 71%